2020
DOI: 10.4028/www.scientific.net/kem.846.122
|View full text |Cite
|
Sign up to set email alerts
|

Machined Surface Roughness Geometry Model Development on Ultrasonic Vibration Assisted Micromilling with End Mill

Abstract: Micro products or micro components are commonly used in today’s world. Research around micromanufacture technologies to produce a better product quality has been going on extensively. Ultrasonic vibration assisted micromilling (UVAM) is one of the technologies that can give a better machining qualities over the conventional ones. One of the benefits UVAM can give is reducing the machined surface roughness. The purpose of this paper is to give an idea how vibration assisted micromilling can give a better surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The ultrasonic processing technology has attracted the attention of scholars and achieved a lot of results [11]. The ultrasonic vibration assisted cutting is one of promising ultrasonic technique, which showed that have great advantages over the conventional cutting, like lower cutting forces, higher machining stability, less tool wear, and a better quality [12,13]. It has been widely used due to…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasonic processing technology has attracted the attention of scholars and achieved a lot of results [11]. The ultrasonic vibration assisted cutting is one of promising ultrasonic technique, which showed that have great advantages over the conventional cutting, like lower cutting forces, higher machining stability, less tool wear, and a better quality [12,13]. It has been widely used due to…”
Section: Introductionmentioning
confidence: 99%